Effect of variable particle size reinforcement on mechanical and wear properties of 6061Al–SiCp composite - Adebisi, Adetayo Abdulmumin; Maleque, Md. Abdul; Ali, Mohammad Yeakub; Bello, Kamil Adeyemi (Taylor and Francis, 2016)
The influence of reinforcement particle size variation plays a major role on the properties of Al–SiCp composite. Therefore, this study aim to investigate the mechanical and wear performance of single particle size (SPS) and multiple particle size (MPS) Al–SiCp composite prepared by stir casting process. The SPS comprises three categories; fine (15 μm), intermediate (40 μm) and coarse (80 μm) particle sizes and combination of the three sizes accounts for the MPS in the ratio 1:1:2, respectively. Oxidation of the SiCp and addition of 1 wt% Mg during composite processing resulted to interface reaction products such as MgO (magnesium oxide) and MgAl2O4 (magnesium aluminate) which suppresses the potential formation of undesired Al3C4 (aluminium carbide). The study reveals that MPS composite improved the hardness and impact properties with enhanced wear performance compared to SPS composite. Characterization of the composite morphology and phases was performed using scanning electron microscope and X-ray diffraction analysis. This study provides an effective method of optimizing the properties of Al–SiCp composite by integrating MPS with low volume fraction of reinforcement phase.